2003
DOI: 10.1097/00005768-200305001-00158
|View full text |Cite
|
Sign up to set email alerts
|

The Induction and Decay of Short-Term Heat Acclimation

Abstract: Abstract:Most advice for heat adaptation is to use long-term (>10 d) regimes, in which hydration status is maintained. We tested the hypothesis that short-term (5-day) heat acclimation would confer substantial improvements in physiological strain and exercise tolerance for exercise in the heat, and fluid regulatory strain provides a thermally-independent stimulus for such adaptations. Ten moderately-fit males were heat acclimated using controlled hyperthermia (rectal temperature 38.5°C) for 90 min on five cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 26 publications
(31 reference statements)
9
65
0
Order By: Relevance
“…However, using our predefined analytical limits (>5 b.min -1 ), meaningful reductions of 4% (TDHA) and 6% (SDHA) were observed in exercising HR from session 1 to 4 with moderate effect, though CON group did not change (1%). This adaptation is typically concurrent with hypervolemia and is suggested to reduce HR 1 b.min -1 , per ∆P (Convertino, 1991), which was present in HA interventions (4.8% TDHA and 5.2% SDHA), consistent with our analytical limits (>5%) and previous research (Nielsen, et al, 1993;Aoyagi, et al, 1994;Patterson, et al, 2004;Garrett, et al, 2009;Lorenzo, et al, 2010). Another key adaptation is reductions in resting and exercising T re of ~0.6% (Garrett et al, 2011), which significantly altered during TDHA, although this was solely contributed by circadian rhythm variations from morning to afternoon sessions.…”
Section: 2supporting
confidence: 91%
See 3 more Smart Citations
“…However, using our predefined analytical limits (>5 b.min -1 ), meaningful reductions of 4% (TDHA) and 6% (SDHA) were observed in exercising HR from session 1 to 4 with moderate effect, though CON group did not change (1%). This adaptation is typically concurrent with hypervolemia and is suggested to reduce HR 1 b.min -1 , per ∆P (Convertino, 1991), which was present in HA interventions (4.8% TDHA and 5.2% SDHA), consistent with our analytical limits (>5%) and previous research (Nielsen, et al, 1993;Aoyagi, et al, 1994;Patterson, et al, 2004;Garrett, et al, 2009;Lorenzo, et al, 2010). Another key adaptation is reductions in resting and exercising T re of ~0.6% (Garrett et al, 2011), which significantly altered during TDHA, although this was solely contributed by circadian rhythm variations from morning to afternoon sessions.…”
Section: 2supporting
confidence: 91%
“…However, despite total phenotypic adaptations occurring within 14 to 21 days during LTHA, ≤ 5 daily exposures during short term HA (STHA) facilitates practically significant thermoregulatory and cardiovascular (~75%) adaptations (Pandolf, 1998), over a more applicable duration for athletes and military personnel. Previous STHA studies (Cotter et al, 1997;Patterson et al, 2004;Sunderland et al, 2008;Garrett et al, 2009Garrett et al, , 2011Costa et al, 2014;Mee et al, 2015;Gibson et al, 2015) have reported physiological and athletic performance improvements within hot conditions. During training, prior to competition or in the lead up to military deployment, STHA may appear more feasible for inclusion in established schedules due to lesser disruption and costs, particularly when tapering and will avoid unnecessary reductions in the quality of training or heat-related illnesses.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Further research should investigate whether the observed reduction in thermal strain with repeated EIMD translates into a meaningful performance improvement. In this regard, its noteworthy that a similar reduction in final exercising Tre (-0.3 °C) during exercise-heat-stress after 5 d heat acclimation brought about a 14% improvement in endurance performance during exercise in the heat (Garrett et al 2009). We can have added confidence in our findings, since a particular strength of the current study is that a comparable control group was used in order to discount confounding heat acclimation or passage of time effects.…”
Section: Discussionmentioning
confidence: 87%